2017
DOI: 10.1136/bmjsem-2017-000295
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of psychosocial risk factors in prevention of low back pain in athletes (MiSpEx)

Abstract: background Low back pain (LBP) is a common pain syndrome in athletes, responsible for 28% of missed training days/year. Psychosocial factors contribute to chronic pain development. This study aims to investigate the transferability of psychosocial screening tools developed in the general population to athletes and to define athlete-specific thresholds.Methods Data from a prospective multicentre study on LBP were collected at baseline and 1-year follow-up (n=52 athletes, n=289 recreational athletes and n=246 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
(39 reference statements)
0
13
0
1
Order By: Relevance
“…They provide insight into a possible interaction between pain and exercise, and its dose-response relationship. Further research in this area is needed for the development of diagnostic tools ( 76 , 77 ) and personalized therapy modules with reinforcing effects for self-management care ( 35 ). This would lead to a great benefit for future therapy and prevention concepts.…”
Section: Discussionmentioning
confidence: 99%
“…They provide insight into a possible interaction between pain and exercise, and its dose-response relationship. Further research in this area is needed for the development of diagnostic tools ( 76 , 77 ) and personalized therapy modules with reinforcing effects for self-management care ( 35 ). This would lead to a great benefit for future therapy and prevention concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Since the etiology of non-specific LBP is indeed multifactorial ( Cholewicki et al, 2005 ), this pathology is not only related to neuromuscular deficits. Psychosocial factors like cognitive beliefs, emotional states, distress, or social context also play an important role related to the appearance and evolution of chronic LBP ( Refshauge and Maher, 2006 ; Wippert et al, 2017 ). These factors were outside the scope of the current study and were not considered in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pain perception and pain modulation in athletes can be different compared to normally active controls ( Tesarz et al, 2012 , 2013 ). Recently, it has been reported that athletes show significantly lower psychosocial risk profiles and prognostic risks compared to non-athletes ( Wippert et al, 2017 ). Although both muscle strength and neuromuscular control of trunk stability have been often investigated in non-athletes, knowledge regarding these properties in elite athletes with and without non-specific LBP is limited ( Trompeter et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some general population psychosocial risk factor assessment tools have been applied successfully to athletes with thresholds being developed for identifying athletes at risk of going on to develop chronic low back pain. 15 Improved understanding and assessment has paved the way for athletic back pain specific biopsychosocial management approaches (neuroscience education and cognitive functional therapy) to be developed. 16 17 Reporting guidelines, injury classification and coding systems have facilitated injury assessment models for a range of common peripheral sports injuries including ankle sprains and femoral acetabular impingement.…”
Section: What Are the New Findingsmentioning
confidence: 99%
“…Some general population psychosocial risk factor assessment tools have been applied successfully to athletes with thresholds being developed for identifying athletes at risk of going on to develop chronic low back pain. 15 Improved understanding and assessment has paved the way for athletic back pain specific biopsychosocial management approaches (neuroscience education and cognitive functional therapy) to be developed. 16 17 …”
Section: Introductionmentioning
confidence: 99%